2021
DOI: 10.1038/s41598-021-95764-3
|View full text |Cite
|
Sign up to set email alerts
|

Population-wide impacts of aspirin, statins, and metformin use on prostate cancer incidence and mortality

Abstract: We evaluated the association between aspirin, statins, and metformin use and prostate cancer (PC) incidence and mortality using a large population-based dataset. 388,760 men who participated in national health screening program in Korea during 2002–2003 were observed from 2004 to 2013. Hazard ratios of aspirin, statins, and metformin use for PC incidence and PC mortality were calculated with adjustment for simultaneous drug use. Cumulative use of each drug was inserted as time-dependent variable with 2-year ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Supported by a Korean study based on claims data of a large population [ 7 ], our study also found a significantly reduced risk of prostate cancer. A Swedish cohort study, nonetheless, suggested no preventive effect of metformin against prostate cancer [ 6 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Supported by a Korean study based on claims data of a large population [ 7 ], our study also found a significantly reduced risk of prostate cancer. A Swedish cohort study, nonetheless, suggested no preventive effect of metformin against prostate cancer [ 6 ].…”
Section: Discussionsupporting
confidence: 71%
“…Statins, as a class of lipid-lowering agents used for hypercholesterolemia treatment and cardiovascular disease (CVD) prophylaxis [ 2 ], are found to be associated with reduced risks of hepatic [ 3 ] and pancreatic [ 2 , 4 ] cancers. The prostate cancer risk among statin users, as opposed to non-users, remains inconclusive, suggested to be reduced [ 5 ], increased [ 6 ], or not significantly associated with use of statins [ 7 ]. Aspirin, a cyclooxygenase and thromboxane inhibitor indicated for pain, inflammation, and CVDs, has shown associations with lowered risks of gastrointestinal cancers, including esophageal [ 8 , 9 ], stomach [ 10 ], liver [ 11 ], and colorectal [ 12 ] cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is one of the main causes of death in the world 1 – 3 . The most common strategies for the treatment of cancer are surgery, radiotherapy, and chemotherapy 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Statin users of at least 6 months had significantly lower risk of esophageal, stomach and colorectal cancer incidence as well as decreased cancer mortality [ 139 ]. Additionally, statin use has also been shown to be associated with decreased incidence in lung [ 140 ], breast [ 141 ], gynecologic [ 142 ], pancreatic [ 143 ] and prostate [ 144 ] cancers. Taken together, statins have a protective effect in preventing cancer incidence in individuals with or without comorbidity risk factors when taken for a prolonged period.…”
Section: Targeting the Mevalonate Pathwaymentioning
confidence: 99%